Emotional Well-being among Middle School Students - Hamad, Ahmed Ibrahim (Journal of Tikrit University for Humanities, 2023)
This research aims to reveal the emotional well-being of middle school students and study the potential impact of each of the gender variables (males - females). The research sample consists of (3794) male and female students. The scale in its final form entails (18) items. The apparent validity of the scale is verified by presenting its clauses to a group of arbitrators, as well as extracting the discrimination coefficient and correlation coefficient for the scale items. The scale’s stability is calculated by re-testing, and it amounted to (0.85). After extracting the validity and stability of the variable (emotional well-being), the researcher applied the scale to the basic research sample consisting of (110) male and female students from the preparatory stage, with males (58) and (52) females. The researcher reaches the following results. 1-Preparatory school students enjoy a good level of emotional well-being 2- There are statistically significant differences between the main scores of the sample members due to the gender variable (males, females)